Generation and characterization of warm dense matter isochorically heated by laser-induced relativistic electrons in a wire target. (13th June 2016) - Schönlein, A.; Boutoux, G.; Pikuz, S.; Antonelli, L.; Batani, D.; Debayle, A.; Franz, A.; Giuffrida, L.; Honrubia, J. J.; Jacoby, J.; Khaghani, D.; Neumayer, P.; et al.
Abstract: We studied the interaction of a high-intensity laser with mass-limited Ti-wires. The laser was focused up to, with contrast of to produce relativistic electrons. High-spatial-resolution X-ray spectroscopy was used to measure isochoric heating induced by hot electrons propagating along the wire up to 1 mm depth. For the first time it was possible to distinguish surface target regions heated by mixed plasma mechanisms from those heated only by the hot electrons that generate warm dense matter with temperatures up to 50 eV. Our results are compared to simulations that highlight both the role of electron confinement inside the wire and the importance of resistive stopping powers in warm dense matter.